Pertolongan Tuhan Terhadap Manusia Pilihan dalam Tiga Karya Sastra The Story Of Little Bird, Ashabul Kahfi dan The Smoke Of Fuji Yama: sebuah Analisis Sastra Bandingan - Muhammad Al-Hafizh (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2011)
There are many folktales that have similiar themes in the world. Birth, love, conflict, struggle for life, and miracle are the universal themes of folktales. Because of these similiarities, there is a great possibility for a reseracher to compare one folktale with others and reaveal the similiarities or differences among them. This article aims at highlightings a popular theme in many folktales around the world, it is about the spritual side of human’s life that gets a miracle from God. That theme is founded in three folktales which originally come from different setting of places, times, and beliefs. The first folktale is The Story of Little Bird. This folktale is a famous one from Irish with Hindy and Chatolic beliefs. The second one is the legend of Ashabul Kahfi from Middle East or Islam world. The third folktale is The Smoke of Fuji Yama, a folktale from Japan that is popular for Shinto believers. Three steps were used in analyzing these folktales. The first step was discussing the time and place of literary work production, including cultural background that set the story. The second step was analyzing literary lements namely character and setting. This step led to the theme of the folktales. The last step was discussing the story structure, such as explanation-rising the conflict-climax-and denounement. The result of analysis shows that theme is the same. It is about a help from God for the choosen and noble craetures.Key terms: literary work, folktale, theme